Nano-Bio- Electronic, Photonic and MEMS Packaging - Wong, C.P; Moon, Kyoung-Sik; Li, Yi (Grace) (Springer US : Imprint: Springer, 2010)
Nanotechnologies are frequently being applied to the biotechnology area, especially in nano material synthesis. Until recently, there has been little research into how to implement nano/bio materials at the device level. Nano-Bio- Electronic, Photonic and MEMS Packaging discusses how nanofabrication techniques can be used to customize packaging for nano devices with applications to biological and biomedical research and products. Covering such topics as nano bio sensing electronics, bio device packaging, NEMs for bio devices and much more, including: Offering a comprehensive overview of nano and bio packaging Discussing nano materials as power energy sources Analyzing nanotubes, superhydrophobic self-clean Lotus surfaces Covering nano chemistry for bio sensor / bio medical device packaging Nano-Bio- Electronic, Photonic and MEMS Packaging is the perfect book for all biomedical engineers, industrial electronics packaging engineers, and those engaged in bio nanotechnology applications research. .